PENGARUH FINANCIAL DISTRESS, LEVERAGE, UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITY TERHADAP KONSERVATISME AKUNTANSI - Muhammad Ali Rif’an; Linda Agustina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
his study aims to determine the effect of financial distress, leverage, firm size, andgrowth opportunity variables on accounting conservatism. The population of thisstudy are transportation companies listed on the Indonesia Stock Exchange for theperiod 2017-2019. The sample selection used purposive sampling technique andproduced 96 sample units. The data analysis technique used the Statistical Packagefor Social Sciences (SPSS) and hypothesis testing with descriptive statistics,inferential statistics, multiple linear regression and hypothesis testing. The resultsshowed that financial distress had a significant negative effect, firm size had asignificant positive effect. Meanwhile, leverage and growth opportunity have noeffect on accounting conservatism. Simultaneously, all dependent variables have aneffect on accounting conservatism. The conclusions obtained from this research arethat accounting conservatism will increase due to high financial distress caused by poor management quality and high political costs in the size of companies that havelarge profits will encourage managers to apply conservative accounting.Simultaneous test results show that financial distress, leverage, firm size, and growthopportunity simultaneously affect accounting conservatism, because there are twovariables of financial distress and firm size affect accounting conservatism, so theresults of the simultaneous test show a significant effect of the four variables.